1997
DOI: 10.1007/bf02505335
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy after myocardial infarction and a coronary artery bypass graft

Abstract: The authors report a pregnancy in a 34 year old patient who previously experienced a myocardial infarction. The pregnancy ended at 39 weeks in the birth of a healthy girl weighting 3040 g, by cesarean section under epidural anesthesia. A review of the literature revealed 33 similar cases, 16 of which were adequately documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The second stage of labor is associated with an increase in hemodynamic and oxidative cardiac stress, likely secondary to strenuous Valsalva necessary for fetal expulsion 4,18,21 . Operative vaginal delivery and a shortened second stage will reduce the amount of Valsalva necessary for delivery, thereby reducing the oxidative stress on the heart 4,18,21,23 . Cesarean section, on the other hand, is associated with an increased risk of hemorrhage, infection and large fluid shifts 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The second stage of labor is associated with an increase in hemodynamic and oxidative cardiac stress, likely secondary to strenuous Valsalva necessary for fetal expulsion 4,18,21 . Operative vaginal delivery and a shortened second stage will reduce the amount of Valsalva necessary for delivery, thereby reducing the oxidative stress on the heart 4,18,21,23 . Cesarean section, on the other hand, is associated with an increased risk of hemorrhage, infection and large fluid shifts 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Dufour et al 18 reported data on pregnancy in patients who had had a previous myocardial infarction with or without prior CABG. In the majority of patients who died, their death occurred at the time of myocardial infarction, and maternal mortality rate was the greatest if myocardial infarction occurred late in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac surgery can be safely done after 28 weeks of gestational age and immediately after cesarean section. [42][43][44] Cardiopulmonary bypass during pregnancy has been associated with a fetal mortality rate of 16% to 33%. During CPB decreasing of maternal mean arterial pressure may cause uteroplacental hypoperfusion, can precipitate uterine contractions.…”
Section: Coronary Artery Bypass Graftingmentioning
confidence: 99%